Os subsistemas recursos humanos: uma análise na prefeitura do município de Parintins-AM - Medeiros, Anaterra Maria Machado (Brasil, 2022)
In this paper, the purpose of this study is to identify if there are traces of the public management in the management of people in the municipality of Parintins, as well as to characterize which practices and instruments are used for personnel administration. Seeking to verify if the management practices of people in the municipal administration of Parintins are directed to the control of personnel, denominated as Personnel Department; if city hall has good management practices of people well elaborated and if the city hall have specific sector of Human Resources and / or People Management. For this study the descriptive research was carried out, using a questionnaire and the participants were the public employees of the Municipality of Parintins.